Educaç\~ao superior e sobre-educaç\~ao no Brasil entre 1980 e 2010 - Maurício Cortez Reis (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This study investigates the pattern of overeducation among Brazilian graduates between 1980 and 2010. Making use of information from the last four population censuses, estimates show that changes in workers' demographic characteristics and shifts in the workers' distribution across fields of study represent around 30% of the 10 percentage points increase in the rate of overeducation verified during this three decades period. Although the distribution of workers across fields of study played an important role, the increase in the rate of overeducation would be substantial even if the workers' profile remained fixed at the 1980 level, when a quite small share of the Brazilian population had a graduate degree.
Keywords: J24; I21; I23; J11; 330; overeducation; tertiary education